Boolean functions with restricted input and their robustness; application to the FLIP cipher - Claude Carlet; Pierrick Méaux; Yann Rotella (IACR Transactions on Symmetric Cryptology, 2017)
We study the main cryptographic features of Boolean functions (balancedness, nonlinearity, algebraic immunity) when, for a given number n of variables, the input to these functions is restricted to some subset E of